Results of open pararenal abdominal aortic aneurysm repair: Tabular review of the literature - Tallarita, Tiziano; Sobreira, Marcone Lima [UNESP]; Oderich, Gustavo S. (Elsevier, 2011)
Open surgical repair of complex abdominal aortic aneurysms requires more extensive dissection and aortic clamping above the renal or mesenteric arteries. Although results of open surgical series have shown variation, morbidity and mortality is higher compared with infrarenal aortic aneurysm repair. Potential complications include renal insufficiency, mesenteric ischemia, multisystem organ failure, and death. Although endovascular treatment with fenestrated and branched endografts might potentially decrease the risk of complications and mortality, its role is not yet defined and the technology is not widely available. Issues related to durability of the procedure and secondary interventions might limit its application to patients with higher risk or those with hostile anatomy. This article summarizes the clinical results of open surgical repair of pararenal abdominal aortic aneurysms to provide a benchmark for comparison with results of endovascular treatment, using fenestrated and branched techniques. © Annals of Vascular Surgery Inc.
Keywords: abdominal aorta aneurysm; adult; aged; aneurysm surgery; cardiovascular risk; clinical decision making; controlled study; endovascular surgery; female; human; major clinical study; male; mortality; open surgery; pararenal abdominal aorta aneurysm; postoperative complication; priority journal; review; surgical technique; treatment outcome; Adult; Aged; Aged, 80 and over; Aortic Aneurysm, Abdominal; Constriction; Dissection; Evidence-Based Medicine; Female; Humans; Male; Middle Aged; Patient Selection; Risk Assessment; Severity of Illness Index; Treatment Outcome; Vascular Surgical Procedures